Recent and active faults and folds in the central-eastern Internal Zones of the Betic Cordillera - Pedrera, A.; Galindo-Zaldívar, J.; Marín-Lechado, C.; García-Tortosa, F.J.; Ruano, P.; López Garrido, A.C.; Azañón, J.M.; Peláez, J.A.; Giaconia, F (Journal of Iberian Geology, 2012)
The most recent tectonic structures of the central-eastern Internal Zones of the Betic Cordillera (from 3.1ºW to 1.7ºW and to the south of 37.525ºN) include fault and folds developed from the Late Miocene onwards, which are related to N-S/NW-SE directed continental collision and moderate thickening of a crust that is relatively hot at depth. In this setting, E-W to WSW-ENE folds, with locally associated E-W transpressive right-lateral and reverse faults, favoured the emersion of the northern Alborán basin palaeomargin and the progressive intramontane basin disconnection. The NNE-SSW to NE-SW trending regional left-lateral Palomares and Carboneras fault zones are dominant structures in the easternmost part of the cordillera. In addition, NW-SE to WNWESE trending normal and oblique-slip normal faults are widespread. The collision is still active and continues to drive active folds and faults, some probably being the likely source of moderate-sized earthquakes. The Campo de Dalías and surrounding sectors, deformed by active ENE-WSW folds and NW-SE to WNW-ESE oblique-slip normal faults, are probably the sites with the largest concentration of significant earthquakes during recent years. Moderate-magnitude earthquakes (Mw 5.0 to 6.5) have occurred there at fairly regular intervals, in 1804, 1910, and 1994. Toward the east, NW-SE trending normal faults extending from Almería to the Tabernas basin deform the Quaternary rocks with associated moderate seismicity (the 2002 Gergal Mw 4.7 earthquake, and possibly the 1894 Nacimiento earthquake, felt with intensity VII). In the Sorbas-Vera basin, the Palomares fault zone is also responsible for moderate-sized earthquakes (1518 Vera earthquake). In the Almanzora corridor, NW-SE to WNW-ESE trending Lúcar-Somontín faults also could be considered one of the possible source of moderate-magnitude seismicity (1932 Lúcar, Mw 4.8 earthquake felt with intensity VIII). Toward the east, between Albox and Partaloa, several small reverse faults and associated compressive structures deform Quaternary alluvial and fluvial sediments. Although some of these folds reveal a slow and progressive deformation from the Middle Pleistocene onwards, some of these reverse fault segments that deform the western Huércal-Overa basin could host the 1972 NW Partaloa, mbLg 4.8 earthquake, felt with intensity VII.